2018
DOI: 10.1186/s12885-018-4862-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucositis associated with anti-EGFR therapy in colorectal cancer: single institutional retrospective cohort study

Abstract: BackgroundChemotherapy-induced oral mucositis impairs the quality of life. The difference in severity of oral mucositis between different anti-epidermal growth factor receptor (EGFR) antibodies combined with cytotoxic drugs in colorectal cancer is unclear. The aim of this study was to investigate the differences in oral mucositis between panitumumab (Pmab) and cetuximab (Cmab) combined with 5-fluorouracil (5-FU).MethodsWe conducted a retrospective cohort study. A total of 75 colorectal cancer outpatients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Although skin and dermatological manifestations have been widely reported as adverse effects in the pharmacological profiles of PD-1 and PD-L1 inhibitors, adverse outcomes involving the oral mucosa have been rare and under-reported with these classes. A single institutional retrospective cohort study found a large incidence of oral mucositis as an adverse effect with the combination of anti-estimated glomerular filtration rate (EGFR) agents such as cetuximab and panitumumab with 5-fluorouracil (5-FU) in the treatment of colorectal cancer [ 3 ]. This study made further conclusions in panitumumab being a bigger culprit than cetuximab in inducing this adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although skin and dermatological manifestations have been widely reported as adverse effects in the pharmacological profiles of PD-1 and PD-L1 inhibitors, adverse outcomes involving the oral mucosa have been rare and under-reported with these classes. A single institutional retrospective cohort study found a large incidence of oral mucositis as an adverse effect with the combination of anti-estimated glomerular filtration rate (EGFR) agents such as cetuximab and panitumumab with 5-fluorouracil (5-FU) in the treatment of colorectal cancer [ 3 ]. This study made further conclusions in panitumumab being a bigger culprit than cetuximab in inducing this adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Mucositis is a common AE noticed in cancer patients on chemotherapy and is associated with poor quality of life [ 48 , 49 ]. Evidence suggests that the incidence of mucositis increases with concomitant administration with EGFR inhibitors such as cetuximab and panitumumab [ 50 ]. Moreover, consistent with our study results, a retrospective cohort study revealed a higher rate of mucositis in patients on panitumumab than those on cetuximab [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the incidence of mucositis increases with concomitant administration with EGFR inhibitors such as cetuximab and panitumumab [ 50 ]. Moreover, consistent with our study results, a retrospective cohort study revealed a higher rate of mucositis in patients on panitumumab than those on cetuximab [ 50 ]. Nonetheless, uncertainty remains about whether the risk of serious mucositis is higher with panitumumab than with cetuximab, but careful monitoring and management of mucositis are warranted especially in panitumumab-treated patients due to potential risks.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the incidence increases signi cantly when chemotherapy is used concomitantly [26]. When used as monotherapy for colorectal cancer treatment, the incidence of oral mucositis does not exceed 10% of patients [27]. During treatment for skin cancer, this adverse effect is not even mentioned as signi cant [28,29].…”
Section: Discussionmentioning
confidence: 99%